Structure Sensitivity in Hydrogenation Reactions on Pt/C in Aqueous‐phase. Issue 1 (26th November 2018) - Sanyal, Udishnu; Song, Yang; Singh, Nirala; Fulton, John L.; Herranz, Juan; Jentys, Andreas; Gutiérrez, Oliver Y.; Lercher, Johannes A.
Abstract: Hydrogenation of phenol and of the benzaldehyde carbonyl group catalyzed by Pt are structure sensitive in aqueous phase. The intrinsic reaction rates are directly proportional to the average size of the Pt particles. This trend is indifferent of the genesis of the reduction equivalents, i. e., dissociation of H2 or proton reduction under cathodic potential. It is concluded that the structure sensitivity is caused by the ensemble size sensitivity of the adsorption of the aromatic molecules, which is favored on (100) and (111) surfaces of larger particles. For electrocatalytic reduction, this structure sensitivity implies that hydrogen evolution increases in rate relative to hydrogen addition to reacting substrates as the size of Pt particles decreases. Abstract : Structure sensitivity : Intrinsic hydrogenation rates of phenol and benzaldehyde in aqueous phase are directly proportional to average size of Pt particles with hydrogen being supplied by both, molecular H2 and in situ by a cathodic potential. In the latter case, it is possible to control the relative rates of hydrogen addition to organics and of H2 evolution using renewable electricity.